Communication Effectiveness Millennial Agriculture Forum (MAF) in Growing Entrepreneurial Motivation of Medan Agricultural Development Polytechnic Students - Misiyem; Mazdalifah; Dewi Kurniawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of the research is to analyze the effectiveness of Millennial Agriculture Forum (MAF) communication in fostering entrepreneurial motivation and analyzing MAF communication barriers in fostering entrepreneurial motivation for Medan Agricultural Development Polytechnic students. Qualitative research method using the constructivism paradigm. The informants in this research were 7 (seven) students because the data was saturated with the criteria for being a student in Semester VIII for the 2023/2024 academic year. The results of the research show that MAF is effective in fostering entrepreneurial motivation because students actively receive information from resource persons, the contents of messages related to entrepreneurship are delivered using the Zoom Meeting application, held on Saturdays with a delivery duration of 2 (two) hours and messages are delivered through slide shows and videos